Correlates of depression and anxiety among the cancer patients in the radiotherapy clinic in UCH, Ibadan, Nigeria (2015)
The diagnosis of cancer and its management result in several problems for cancer patients. This may result from factors some of which may be modifiable. This study was aimed at identifying the prevalence of depression and anxiety in patients attending the Radiotherapy Clinic in the UCH, Ibadan and to identify the variables affecting them. The Beck’s Depression Inventory (BDI-II) and the Fear of Progression (FOP12) scales were used to assess depression and anxiety among cancer patients. The 206 diagnosed cancer patients studied were made up of 146 (79.6%) women and 42 (20.4%) men. Some 76 (36.9%) had moderate to very high anxiety while 29 (14.1%) had borderline to severe depression. The ages ranged between 10 to 85 years with a mean of 47.84 (+/_ 16.45). In prevalence of anxiety and depression, 36.9% of the cancer patients experience varying levels of anxiety and 31.6% experience varying levels of depression. On logistic regression, age, religion, educational level and treatment type significant factors for anxiety. Specifically, being older than 40years, being a Christian, not reporting educational qualification and not yet commencing treatment compared to having surgery as the current treatment type was significant risk factors for anxiety. Only treatment type was a significant risk factor for depression that is not yet commencing treatment compared to having surgery as the current treatment type was a factor for depression. Appropriate Psychological evaluation and therapy as may be needed should be administered to all oncology patients preparing for surgery and chemotherapy to enhance their emotional and psychological wellbeing. The findings of this study have implication for establishment of psycho-oncology care in all the cancer centres in Nigeria.